WEEKLY TEST DAY MILK YIELD AND LACTATION MILK YIELD IN HF X GIR HALFBRED (Indian Journal of Animal Production and Management, 2016)
The data on milk production performance of 342 HF X Gir halfbreds were collected from records maintained  at Research Cum Development Project on Cattle, Mahatma Phule Krishi Vidyapeeth, Rahuri (Maharashtra)  for a period from year 1974 to 2013. Overall mean of 43 individual weekly test day milk yield varied from  3.16±0.14 kg (WTDY43) to 13.52±0.14 kg (WTDY5). The overall mean lactation milk yield was 3457.33 ±  41.79 kg. Effect of period of calving on all 43 weekly test day milk yield was significant (Ps
Keywords: Gir; Lactation milk yield; Test day milk yield